(3TQM JgPjH GdcdGe hGdefWbs - (3GdUOjbj, GdOhGfj, LdGd GdOjf, eMeO Hf CSYO J (B918 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; JgPjH GdefWb hGdcdGe JhTjMI HPcQ GdeaVd GdefYGe hHYO agPg YLGdI fGaYI HefWb GdJgPjHs
(3BNQgG (B:s
(3GdeWdbI GdKHhJ HMSH faS GdCeQ jMce HeG dG jajO EdG JZjQG aj GdbGYOI GdeegOI aj fSH GdbVGjG hcPG ef CNP aj GdeTQWI KHhJ GdeMehd HGdEecGf HGdaYd Ydi Cfg dG ojYGOs
(3aj Chdg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 32s
(3eYLe GdeDdajf (B3 / 126s
(3cTa GdXfhf (B1 / 515 - 516s
(3TPQGJ GdPgH (B8 / 160s
Keywords: (3GdadSaI hGdefWbs